Laser powder bed fusion of diamond/N6 MMCs enabled by Ni-Ti coated diamond particles. (May 2022) - Zhang, Sheng; Ding, Minglu; Wang, Lu; Ge, Wenjun; Yan, Wentao
Graphical abstract: Highlights: The wettability between diamond and nickel is improved by coating thin layers of Titanium and Nickel on diamond particles. The deformation mechanism of the composites powder during ball milling is summarized. The distribution of the diamond particles in the single track is simulated to explain the diamond agglomeration during the LPBF. Abstract: Metal matrix composites (MMCs) have received increasing attention and there is a growing interest in additive manufacturing (AM) of MMCs with complex shapes recently. However, it remains challenging to control the quality of composite powder for MMCs. In this study, the diamond particles are firstly coated with thin layers of Titanium and Nickel to ensure strong interface bonding with the Nickel matrix. The influence of ball milling parameters on the Ni-Ti coated diamond/N6 composite powder particles preparation and the effect of processing parameters during laser powder bed fusion (LPBF) on the densification of and defects in the fabricated samples are analyzed. In the ball milling stage, the results show that highly flowable composite powder particles for LPBF can be obtained under a ball milling time of 4 h, a speed of 250 rpm, and a ball-to-powder ratio of 2:1. With the optimized composite powder, a set of Ni-Ti coated diamond/N6 MMCs are further manufactured under the laser powers of 150, 160, and 170 W and scanning speed of 250 mm/s, the MMC samples have relative densities higher than 99%. Our study demonstrates the feasibility of manufacturing dense diamond/N6 and other similar MMCs with appropriate coating, ball-milling and LPBF parameters.